Determinan Kepuasan Menyusui: Analisis Faktor Sosiodemografi, Obstetri, dan Praktik Menyusui Pada Ibu - Syariffah Jihadilah; Iffah Indri Kusmawati; Rufidah Maulina; Luluk Fajria Maulida; Siti Nurhidayati (STIKES Bina Usada Bali, 2026)
Background: The exclusive breastfeeding coverage at Polokarto Public Health Center in 2023 was 34.8%. Two out of five mothers had low breastfeeding satisfaction. Approximately two out of five mothers reported low breastfeeding satisfaction. Although breastfeeding is generally perceived as a rewarding and fulfilling experience, many mothers encounter various challenges during the early postpartum period that may adversely affect their satisfaction with breastfeeding. Methods: This study used a cross-sectional design. Breastfeeding satisfaction was measured using the Maternal Breastfeeding Evaluation Scale questionnaire. A total of 100 respondents were recruited using accidental sampling. Data were analyzed using bivariate analysis and multivariate analysis with binary logistic regression. Results: Bivariate analysis showed that parity, breastfeeding method, and breastfeeding problems were associated with breastfeeding satisfaction. Multivariate analysis showed only breastfeeding method and breastfeeding problems remained significantly associated with breastfeeding satisfaction. Mothers who did not breastfeed directly had lower odds of having high breastfeeding satisfaction compared with those who practiced direct breastfeeding (AOR = 0.015; 95% CI = 0.001–0.212; p = 0.002). Mothers who experienced breastfeeding problems also had lower odds of having high breastfeeding satisfaction compared with those without breastfeeding problems (AOR = 0.199; 95% CI = 0.041–0.971; p = 0.046). Conclusion: Breastfeeding method and breastfeeding problems were the factors most strongly associated with breastfeeding satisfaction among mothers in the working area of Polokarto Public Health Center. Midwifery support in promoting direct breastfeeding, early detection of lactation problems, and management of breastfeeding complaints should be strengthened to improve maternal comfort and positive breastfeeding experiences